Not All Behind Closed Doors: Examining Bystander Involvement in Intimate Partner Violence. Issue 18 (September 2019) - Taylor, Elizabeth; Banyard, Victoria; Grych, John; Hamby, Sherry
It is often said that intimate partner violence (IPV) happens "behind closed doors"; however, research on IPV and other crimes suggests that witnesses are sometimes present. This suggests that bystanders may be in a position to help victims or potential victims of violence. Bystander behavior has been studied primarily in school settings, and consequently, little is known about how often it occurs or what its effects may be in the broader community. This study examined IPV incidents in a rural sample to assess the presence and potential impact of bystanders on victim-reported outcomes. One thousand nine hundred seventy-seven adult participants completed a questionnaire that asked about five violent behaviors (my partner threatened to hurt me; pushed, grabbed, or shook me; hit me; beat me up; sexually assaulted me), bystander characteristics, and victim outcomes (fear; injury; disruption of daily routines; mental health). Adult or teen bystanders were present for each IPV approximately one third of the time, except in the case of sexual assault (14.3%). When a bystander was present, victims reported higher rates of injury, greater disruption in their routines, and poorer mental health. When a bystander's safety was threatened, victims reported more physical injury and more routine disruption. A considerable number of IPV incidents do not happen behind closed doors, and the presence of a bystander was associated with worse outcomes for victims. Prevention efforts for adult IPV may need to take a more cautious or nuanced approach to encouraging bystander action, especially when confronted with more severe incidents. Bystander safety should be a priority for violence prevention.